2009
DOI: 10.1002/pssc.200982576
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence in Er‐doped AgGaS2–GeS2 glasses

Abstract: In this work study of photoluminescence (PL) spectra in the Er‐doped glasses of the AgGaS2‐GeS2 system is presented. Emission spectra of the glasses at T ≈ 292 K, excited by light with λex ≈ 980 nm and λex ≈ 532 nm are described well by transitions in the 4f‐shell of Er3+ ions. Spectral curves of the emission can be deconvoluted into four Gaussian components. Er atoms are localized both in the glass matrix and (with increased concentration) around large structural damages (heterogeneities) which are drains for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The PL spectra and emission mechanism in non-irradiated glassy alloys have been investigated in our previous works (Halyan et al, 2013(Halyan et al, , 2009. In those samples, we registered PL peaks at the wavelengths 520, 657 and 855, 1540 nm, which corresponds to the transitions 2 H 11/2 -4 І 15/2 , 4 F 9/2 -4 І 15/2 , 4 S 3/2 -4 І 13/2 , 4 I 13/2 -4 І 15/2 in erbium ions Er 3 þ , respectively.…”
Section: Photoluminescencementioning
confidence: 99%
“…The PL spectra and emission mechanism in non-irradiated glassy alloys have been investigated in our previous works (Halyan et al, 2013(Halyan et al, , 2009. In those samples, we registered PL peaks at the wavelengths 520, 657 and 855, 1540 nm, which corresponds to the transitions 2 H 11/2 -4 І 15/2 , 4 F 9/2 -4 І 15/2 , 4 S 3/2 -4 І 13/2 , 4 I 13/2 -4 І 15/2 in erbium ions Er 3 þ , respectively.…”
Section: Photoluminescencementioning
confidence: 99%
“…Among the glassy alloys investigated here, the PL band widens in the sample with 0.27 at.% Er, and the above inequality is fulfilled. The microstructure study of alloys [11] showed the existence of inhomogeneities of 6-7 μm size the concentration of which increases with the amount of erbium. The generated inhomogeneities are good drains of defects which serve as the basis for cluster formation.…”
Section: Photoluminescence In Chalcogenide Glassesmentioning
confidence: 99%
“…Сьогодні ербієві стекла і кристали широко використовуються в якості активного середовища в лазерах і оптичних підсилювачах. Це пов'язано з тим, що довжина хвилі генерації йона ербію (1,5 мкм) є оптимальною для передачі інформації по волоконнооптичних лініях зв'язку та лежить у безпечному для очей діапазоні довжин хвиль [1][2][3][4][5]. У таких пристроях необхідний коефіцієнт підсилення може бути досягнутий за рахунок збільшення концентрації йонів Er 3+ .…”
Section: вступunclassified